2016
DOI: 10.1098/rspb.2016.1536
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic innovation through recombination in genome-scale metabolic networks

Abstract: Recombination is an important source of metabolic innovation, especially in prokaryotes, which have evolved the ability to survive on many different sources of chemical elements and energy. Metabolic systems have a wellunderstood genotype-phenotype relationship, which permits a quantitative and biochemically principled understanding of how recombination creates novel phenotypes. Here, we investigate the power of recombination to create genome-scale metabolic reaction networks that enable an organism to survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…EGCs not only affect the accurate representation of existing metabolic systems. They will be particularly problematic in evolutionary simulations that involve the incorporation of foreign metabolic reactions from other species [ 28 30 ]. Such mixing of reactions from disparate model reconstructions may easily introduce EGCs, and may thus lead to erroneous phenotype predictions.…”
Section: Resultsmentioning
confidence: 99%
“…EGCs not only affect the accurate representation of existing metabolic systems. They will be particularly problematic in evolutionary simulations that involve the incorporation of foreign metabolic reactions from other species [ 28 30 ]. Such mixing of reactions from disparate model reconstructions may easily introduce EGCs, and may thus lead to erroneous phenotype predictions.…”
Section: Resultsmentioning
confidence: 99%
“…First, recombination is a ubiquitous force of genetic change, not only in eukaryotes but also in prokaryotes whose genomes are being continually reorganized through horizontal gene transfer. Second, in contrast to smaller-scale genetic change, such as point mutations, recombination causes larger-scale genetic change with greater potential to create novel phenotypes (27)(28)(29)(30)(31)(32). Thus, if we found that phenotypic evolution was constrained when recombination causes genotypic change, it would be even more constrained if point mutations caused such change.…”
Section: Introductionmentioning
confidence: 87%
“…transferred from donor to recipient, and that can lead to metabolic innovation. For this analysis, it is relevant that the majority of metabolic innovations is caused by the transfer of a single key reaction (32). We analyzed transferable reactions in greater depth, focusing on all 1000 parental donor metabolic networks viable on a given carbon source C i , and on the (D/2 ¼ 50) reactions that are present in the donor metabolic network, but are absent in the recipient, and so can potentially be transferred from the donor to the recipient.…”
Section: On the Underlying Causes Of Constraints And Contingenciesmentioning
confidence: 99%
“…While an experimental assessment of the landscape of possible variants of metabolism with different coenzyme systems would be extremely challenging, one can leverage theoretical and computational approaches to help address these questions. The recent development and application of metabolic modeling has brought a quantitative and model-driven approach to the study of metabolic evolution (17)(18)(19)(20)(21), and has led to uncovering optimality criteria that may have shaped universal features of core metabolism, such as the emergence of both NAD(H) and NADP(H) (22). Although recent quantitative work has explored the logic for why NAD(P)H emerged as a prominent coenzyme in biochemistry (23), the forces that drove the emergence of both NAD(H) and NADP(H), rather than just a single coenzyme, remain unclear.…”
Section: Introductionmentioning
confidence: 99%